2009
DOI: 10.1111/j.1755-3768.2009.01609.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic interference with EphrinB2 signalling inhibits oxygen-induced angioproliferative retinopathy

Abstract: ABSTRACT.Purpose: To investigate whether EphrinB2 (EfnB2) or EphB4 influence retinal angiogenesis under physiological or pathological conditions. Methods: Using the mouse model of oxygen-induced proliferative retinopathy (OIR), the expression of EfnB2, EphB4, vascular endothelial growth factor (VEGF), VEGFR1 and VEGFR2 was quantified by quantitative polymerase chain reaction (qPCR) and localized in EfnB2-and EphB4-lacZ mice. Angioproliferative retinopathy was manipulated by intravitreal injection of dimeric Ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…These results indicated that ephrin-A4 is another potential target against retinal NV, and further studies should be conducted to determine the value of its clinical application. Ephrin-B2, EphB4, and EphA2 have previously been shown to be involved in retinal neovasculogenesis [7][8][9][10][11] ; ephrin-A4 is a new member of the Eph/ephrin molecule family involved in the process of retinal NV. Further studies on the Eph/ephrin signaling system may identify other genes that control the retinal angiogenesis process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that ephrin-A4 is another potential target against retinal NV, and further studies should be conducted to determine the value of its clinical application. Ephrin-B2, EphB4, and EphA2 have previously been shown to be involved in retinal neovasculogenesis [7][8][9][10][11] ; ephrin-A4 is a new member of the Eph/ephrin molecule family involved in the process of retinal NV. Further studies on the Eph/ephrin signaling system may identify other genes that control the retinal angiogenesis process.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Ephrin-B2, EphB4, and EphA2 have been shown to be involved in retinal neovasculogenesis. [7][8][9][10][11] A comparative retinal gene expression analysis in two rodent models of oxygen-induced retinopathy (OIR) identified increased expression levels of members of the VEGF and ephrin receptor signaling pathways in both models. 12 These previous studies underscore the role of the Eph/ephrin signaling pathway in retinal NV and suggest that further studies on the Eph/ephrin signaling pathway in the ROP would help to further understand the mechanism of retinal NV and to find new treatment opportunities.…”
Section: R Etinal Neovascularization (Nv) Is Characteristic Of Retinomentioning
confidence: 99%
“…10,11 In addition, EphB4 has been shown to be overexpressed in a wide range of tumor cells and tissues, including cancers found in the ovary, 12 bladder, 13 prostate, 14,15 breast, 16 and colon. 17,18 These findings have qualified EphB4 as an interesting angiogenic target for antitumor and antiretinopathic therapies, and different approaches have been taken to target EphB4, including small molecules, [19][20][21][22][23][24][25] peptides, 26 soluble extracellular domains, 11,[27][28][29][30][31] or functional blocking antibodies. [32][33][34] On the molecular level, ligand-receptor interactions in the Eph family are characterized by clustering of the proteins at the membrane followed by bidirectional intracellular signaling events into both the Eph receptor expressing cell and the ephrin expressing cell.…”
mentioning
confidence: 97%
“…qPCR was performed using standard methods [17,19]. RT-PCR was performed with CNV-RPE-69 but was not possible for CNV-RPE-88 as the amount of material was limited.…”
Section: Microarray Analysismentioning
confidence: 99%